Bifurcations, Instabilities and Degradations in Geomaterials - Wan, Richard.; Wan, Richard.; Alsaleh, Mustafa.; Alsaleh, Mustafa.; Labuz, Joe.; Labuz, Joe. (Springer Series in Geomechanics and Geoengineering,, 2011)
Geomaterials exhibit complex but rich mechanical behaviour with a variety of failure modes ranging from diffuse to localized deformation depending on stress, density, microstructure, and loading conditions. These failure modes are a result of an instability of material and/or geometric nature that can be studied within the framework of bifurcation theory. Degradation is another related phenomenon arising from cyclic loading, ageing, weathering, chemical attack, and capillary effects, among others. The methodology of analyzing the various types of instabilities is crucial in the adequate modelling and safe design of numerous problems in geomechanics. The present volume contains a sampling of enlarged versions of papers presented at the International Workshop on Bifurcation and Degradations in Geomaterials (IWBDG 2008) held in Lake Louise, Alberta, Canada, May 28-31, 2008. These papers capture the state-of-the-art in the specialized field of geomechanics and contemporary approaches to solving the central issue of failure. Some engineering applications are presented in the areas of energy resource extraction and soil-machine interaction.    .